Real‐life effectiveness of tildrakizumab in chronic plaque psoriasis: A 52‐week multicentre retrospective study—IL PSO (Italian landscape psoriasis). (5th October 2022) - Narcisi, Alessandra; Valenti, Mario; Gargiulo, Luigi; Ibba, Luciano; Amoruso, Fabrizio; Argenziano, Giuseppe; Bardazzi, Federico; Burlando, Martina; Carrera, Carlo Giovanni; Damiani, Giovanni; Dapavo, Paolo; Dini, Valentina; et al.
Abstract: Background: Tildrakizumab is a humanized monoclonal antibody that binds selectively the p19 subunit of interleukin‐23. It is approved for treatment of moderate–severe chronic plaque psoriasis. Objectives: We conducted a 52‐week retrospective study to assess the effectiveness and safety of tildrakizumab in a real‐life setting. Methods: Our retrospective study included 237 consecutive adults with moderate‐to‐severe plaque psoriasis, enrolled in 10 different Italian centres, treated with tildrakizumab up to Week 52. Patient characteristics, comorbidities, previous treatments and the PASI (Psoriasis Area and Severity Index) score at each visit (baseline, Week 16, Week 28 and Week 52) were retrieved from the electronic medical records. The percentages of patients achieving 75%, 90% and 100% (PASI 75, PASI 90 and PASI 100) improvement in PASI with respect to baseline PASI were registered. Results: At Week 52, 90.91%, 73.55% and 58.68% of patients achieved a PASI reduction ≥75% (PASI 75), PASI 90 and PASI 100, respectively. An absolute PASI ≤ 2 was reached by 85.95% at Week 52. Compared with Phase 3 clinical trials, we observed similar rates of PASI 75/90 responses and higher percentages of patients achieving PASI 100. Patients who had not responded to previous biologic treatments and patients with cardio‐metabolic comorbidities were significantly more likely to achieve PASI 100 at Week 28 and PASI 90 at Week 52. The higher body mass index did not interfere with the odds of reaching PASI 75/90/100 at each time point. No significant safety findings were recorded throughout the study, and none of the patients had to interrupt the treatment because of adverse events. Conclusion: Our data suggest that the efficacy of tildrakizumab for plaque psoriasis in 'real‐life' clinical practice is comparable with Phase 3 clinical trials with higher percentages of patients achieving complete skin clearance (PASI 100) at Weeks 16, 28 and 52.